2019
DOI: 10.1007/s00395-019-0753-y
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to nocturnal train noise induces endothelial dysfunction and pro-thromboinflammatory changes of the plasma proteome in healthy subjects

Abstract: Nocturnal train noise exposure has been associated with hypertension and myocardial infarction. It remains unclear whether acute nighttime train exposure may induce subclinical atherosclerosis, such as endothelial dysfunction and other functional and/or biochemical changes. Thus, we aimed to expose healthy subjects to nocturnal train noise and to assess endothelial function, changes in plasma protein levels and clinical parameters. In a randomized crossover study, we exposed 70 healthy volunteers to either bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 53 publications
3
77
0
3
Order By: Relevance
“…These results demonstrate that Exenatide exerts protective effects on cardiomyocytes through the NF-κB signaling pathway, in agreement with previous studies [42,43]. Indeed, such studies have shown that inhibition of NF-κB prevents heart inflammation [44,45] while improving oxidative stress and countering the downregulation of anti-oxidative factors [46,47]. In addition, myocardial damage induced by a high-fat diet was also normalized by NF-κB inhibition [48].…”
Section: Agingsupporting
confidence: 91%
“…These results demonstrate that Exenatide exerts protective effects on cardiomyocytes through the NF-κB signaling pathway, in agreement with previous studies [42,43]. Indeed, such studies have shown that inhibition of NF-κB prevents heart inflammation [44,45] while improving oxidative stress and countering the downregulation of anti-oxidative factors [46,47]. In addition, myocardial damage induced by a high-fat diet was also normalized by NF-κB inhibition [48].…”
Section: Agingsupporting
confidence: 91%
“…The important role of oxidative stress and inflammation for noise-induced cardiovascular complications was also supported by changes of the plasma proteome, centred on redox, pro-thrombotic and proinflammatory pathways, in subjects exposed to train noise for one night [mean SPL 54 dB(A)]. 30 …”
Section: Pathophysiology and Epidemiology Of Noise And Cardiovascularmentioning
confidence: 99%
“…Endothelial dysfunction is regarded as an early key event in the development of manifest cardiovascular disease with studies indicating its predictive role for the future development of cardiovascular events and mortality risk [ 35 ]. Indeed, experimental animal and human studies have shown that traffic noise-induced autonomic perturbation and sympathoadrenal activation lead to increased levels of circulating stress hormones and oxidative stress-induced endothelial dysfunction accompanied by the release of proinflammatory mediators, increased oxidative stress [ 9 , 10 , 24 , 28 ], and activation of prothrombotic pathways [ 12 ]. Thus, MR-proANP may reflect a compensatory mechanism to reduce the cardiovascular load in response to increased noise stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, mechanistic insight by which noise triggers detrimental effects on the cardiovascular system is still elusive. Recent human studies suggest that traffic noise exposure causes the release of stress hormones and inflammatory signaling molecules leading to oxidative stress and subsequent endothelial dysfunction and arterial stiffening [ 9 12 ]. We have also demonstrated that noise annoyance is associated with a higher risk of prevalent atrial fibrillation, which was further accompanied by an increased trend of midregional pro atrial natriuretic peptide (MR-proANP) plasma levels [ 13 ].…”
Section: Introductionmentioning
confidence: 99%